Reducing impulsivity in repeat violent offenders: an open label trial of a selective serotonin reuptake inhibitor - Butler, Tony; Schofield, P.; Greenberg, D.; Allnut, S.; Indig, D.; Carr, V.; D'Este, C.; Mitchell, P.; Knight, L.; Ellis, A. (Taylor & Francis Ltd, 2010)
Background: The association between serotonergic dysfunction and aggression hasprompted the use of selective serotonin re-uptake inhibitors (SSRIs) as a means of controllingimpulsive violent behaviour. The aim of the current study was to examine the feasibilityof using an SSRI to treat impulsivity in a group of repeat violent offenders.Methods: Potential participants were recruited from three magistrates ’ court complexes inthe Sydney metropolitan area and all had histories of violent offending (at least one priorconviction for a violent offence). Those who scored highly on the Barratt Impulsivity Scale(BIS-11), passed medical and psychiatric evaluations and consented to treatment wereprescribed sertraline (Zoloft) over a three month period.Results: Thirty-four individuals commenced the trial, with 20 completing the three month intervention.Reductions were observed across a range of behavioural measures from baseline to3 months: impulsivity (35%), irritability (45%), anger (63%), assault (51%), verbal-assault(40%), indirect-assault (63%), and depression (62%). All those who completed the three monthtrial requested to continue sertraline under the supervision of their own medical practitioner.Conclusion: Our fi ndings suggest that treating impulsive violent individuals in the criminaljustice system with an SSRI is a potential treatment opportunity for this population. Anadequately powered randomized control trial of this intervention is warranted.Key words: .